Enhanced photoeletrocatalytic reduction dechlorinations of PCP by Ru-Pd BQDs anchored Titania NAEs composites with double Schottky junctions: First-principles evidence and experimental verifications - Fan, S.; Li, X.; Tan, J.; Zeng, L.; Yin, Z.; Tade, Moses; Liu, Shaomin (Elsevier BV, 2018)
Novel palladium (Pd) and ruthenium (Ru) Bimetal Quantum Dots (BQDs) co-anchored on Titania nanotube arrays electrodes (NAEs) bearing double Schottky junctions with superior photoelectrochemical conversions and photoelectrocatalytic reductive dechlorination (PECRD) properties were successfully developed and constructed by facial two-step electrochemical strategy. The PECRD of toxic Pentachlorophenol and photoelectrochemical conversions over the afore-designed bimetallic Pd and Ru BQDs co-anchored TiO2 (101) nanotube array electrodes (Ru-Pd BQDs/TiO2 NAEs) composites have been systematically investigated both theoretically and practically. A remarkable enhancement of photoelectrochemical conversion efficiency of 14.10% as compared to that of the pure TiO2 NAEs (0.45%) in the Ru-Pd BQDs/TiO2 NAEs composites has been successfully achieved, and pentachlorophenol (PCP) species could be PECRD over 90% under the optimum conditions. Various physico-chemical techniques including UV–vis spectroscopy, XRD, SEM/TEM/EDX, PL, EIS, SPV and XPS were employed to systematically characterize the crystal-, electronic and micro-interfacial structures of the composites with double Schottky junction, respectively. All of the studies implied that the marvelous enhancement of separation efficiency of photo-generated electron–hole pairs is mainly caused by the Schottky-barriers as derived from the interfacial interaction within the Ru-Pd BQDs/TiO2 NAEs metal-semiconductor composites. The Ru-Pd BQDs/TiO2 NAEs bearing double Schottky-junctions would greatly facilitate the interfacial charge transfer followed by fully utilization of the photo-generated electrons for PECRD of PCP species. The DFT calculations clearly indicated that the number of impurity (i.e., co-anchored Ru-Pd BQDs) energy levels near Fermi surface increased, promoting electron energy transition and reduces the band gap, which suggesting a better reduction capability. Overall, this work shall provide brand new insight for molecular design of Bimetal Quantum Dots (BQDs) assembled onto Tatiana NAEs composites with superior performance for both environmental eliminations and green energy conversions and could significantly deepen our understanding to the catalytic dechlorination pathways of typical environmental toxic polychlorinated compounds over multifunctional nanocatalytic materials.